Analysis of noise components of microwave diode oscillators - Meniailo, O.D.; Grigorieva, O.V. (Radiotekhnika, 2025)
The work deals with theoretical and practical study of fluctuation components of diode oscillators. The mechanism of formation of fluctuation components of diode oscillators is considered. An experimental study of fluctuation components of oscillators is carried out. A generator on an avalanche-transit diode was chosen as an example of a diode autogenerator with a fairly high level of its own noise. According to the results of research into amplitude-modulated and frequency-modulated noise components of an oscillator on an avalanche-flying diode depending on the quality factor of its oscillatory system, the exponential nature of these dependencies, predicted by the results of theoretical analysis, is observed, The conducted studies indicate the consistency of theoretical conclusions with practical results. The conclusions of the research can be used in the design of microwave diode generators with specified fluctuation characteristics.